A dynamic resource allocation scheme based on cognition in LTE system. (30th May 2019) - Wang, Junshe; Wang, Yanfei; Wang, Songhua
In this paper, we propose a dynamic spectrum allocation scheme based on cognition in the LTE system. The new scheme is to address the poor communication service problem caused by co-channel interference between the cell-edge users in the LTE system. The scheme leverages the cognitive characteristic in the LTE system to enable the base station to dynamically obtain the idle resource status information of the adjacent cells and integrates the idle resource information of the target cell, and then employs the ant colony optimisation technique to allocate the resource blocks to users. Experimental results show that the proposed scheme allows the cell-edge users to dynamically utilise the idle resource blocks of adjacent cells, which enhances resource blocks utilisation and system throughput while ensuring fairness among users, thus may improve the quality of user service at the cell-edge.